Dynamics of Tax Aggressiveness: Audit Committee Moderation on Corporate Characteristics - Yudea F Anai; Dika Karlida Sari; Muhammad Andika Prasetya (Universitas Widyatama, 2025)
Tax aggressiveness is a major concern for policymakers and corporate governance stakeholders because of its impact on state revenues and corporate financial strategies. This study aims to evaluate the influence of company size, capital intensity, and CSR on tax aggressiveness, with the audit committee as the moderation variable. This study adopts a quantitative method using secondary data from industrial sector companies listed on the IDX during the period 2021 to 2023. To analyze the relationship between variables, multiple regression techniques and MRA were used. The results show that capital intensity has a negative impact on tax aggressiveness, which shows that companies with large investments in fixed assets tend to have lower levels of tax aggressiveness due to depreciation benefits. However, company size and CSR did not show a significant influence on tax aggressiveness, contrary to some previous research findings. In addition, the audit committee was proven to significantly moderate the relationship between capital intensity and tax aggressiveness, emphasizing the importance of corporate governance roles in overseeing tax policies. However, the audit committee's moderation of the relationship between company size and CSR with tax aggressiveness did not show significant results, indicating that additional governance mechanisms may be necessary. The results of this study enrich the literature related to tax strategies and corporate governance and offer implications for regulators, company executives, and investors in developing more effective policies to increase transparency and tax compliance.